KORELASI ANTARA NEURON-SPECIFIC ENOLASE SERUM DAN GLASGOW COMA SCALE DI PASIEN CEDERA KEPALA - Usi Sukorini; Isti Setijorini Wulandari; Budi Mulyono; Handoyo Pramusinto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
The outcome after head injury is mostly determined by Glasgow Coma Scale (GCS) and the degree of brain damage which reveals.CT scan is also important to assess its severity. However relatively it is not in a less costly manner and sometimes patients mobilisationare needed. Brain damage due to traumatic head injury refers to homeostasis unbalance, and it is the important causes of releasingbiochemical analyte from neuron via injured blood brain barrier to circulation. Neuron-specific enolase as a glycolytic enzyme in neuroncytoplasm might increase. Hopefully, measurement of NSE levels can provide information about the extent of the disease. The objectiveof the study is to test the correlation between the Neuron Specific Enolase (NSE) serum as a one of biochemical marker of brain injuryand the GCS. For this purpose, a cross sectional, analytical observasional study was carried out at the Emergency Departement andDepartement of Clinical Laboratory, Sardjito General Hospital, Yogyakarta, Indonesia. Fifty-one patients selected by an eligible criteriawere included in the study, which consist of severe, moderate and mild head injury. Blood samples were collected and serum NSE wasmeasured by immunoanalyzer using Electro Cheluminescence ImmunoAssay (ECLIA). Chi square test was used to test the differenceproportion of the group: NSE ≥ 21.7 ng/mL and NSE < 21.7 ng/mL according to measured variables, and Spearman correlation testwas used to correlate serum NSE and GCS, and other variables. In the study fifty-one patients with head injury were included, 74.5%of patients were males and 68.6% is in the age of 15–45 years old. The patients were further divided into two groups on the basis ofserum NSE ≥ 21.7 ng/mL and < 21.7 ng/mL; the former group was dominated by severe head injury patients (54.1%). In addition, aproportion of non survivors (66.6%) in group NSE ≥ 21.7 ng/mL was higher compared to those in NSE < 21.7 ng/mL group. Moreover,a large number of mild head injury (95.45%) and survivors (83.33%) had lower serum NSE (< 21.7 ng/mL). In the study, was found anegative correlation between serum NSE and GCS (r = -0.552; p = 0.00). Also, serum NSE were inversely correlated with blood kaliumand hemoglobin (r = -0.162; p = 0.027 dan r = -0.376; p = 0.009), in contrast with leucocytes count (r = 0.485; p = 0.001). Theconclusion so far there was a negative correlation between serum NSE and GCS. It is suggested that neuron-specific enolase can be veryuseful as a biochemical marker in assesssing the severity of head injury. Therefore, it is nessessary to carry out the prognostic study toknow to what extent it can predicting the outcomes.